Bhārata kā Mukti Saṅgharsha aura Rūsī Krānti - Upādhyāya, Viśvamitra, 1933- (Navayuga Pabliśarsa, 1980)
India-Soviet relations, 1905-1921; a study in the light of the impact of the Bolshevik Revolution on the Indian Independence struggle.